Desenvolvimento pleno de adolescentes nativos digitais: um estudo sobre as possíveis metodologias de ensino - Kipnis, Marina Vasconcelos (2018)
Nowadays the society is in an era where technologies are developing more and more immersed in this scenario, there is a generation called, Digital Natives (PRENSKY, 2001). This generation is marked by not understanding a world without the use of technologies. Starting from this reality, this study sought to understand first, if our education is aware of the presented scenario, in the sense of adapting to the technologies and understanding the lifestyle of the digital natives, in the perspective of full formation. In the face of this questioning, the present study applied a research on a private school in Distrito Federal. The procedure used were an analysis the proposal contained in it’s pedagogical political project, the observation of two classes, recorded interviews with two teachers and application of a questionare with the students, wich were qualified as representatives of digital natives. According to the results, the main proposal of the school works with the integral formation of its students, articulating this concept with the full training of the subject. The observations and interviews showed a sensitivity of both teacher to recognize outstanding differences between their students and themselves when they were at the same age group, and they were open to innovate in their methodologies at all times. The students were satisfied with the lessons received at the school if they lost a little in relation to the use of this technology, even though it’s a feature characteristic of this generation, which may be due to the limitation of acess to digital technologies, both by the schoo and the family. It is understood that there are important aspects regarding the full training and its adequacy to deal with the current society.